Modelling equity valuation based on accounting policy for investment property / Mohd Halim Kadri, Juyati Mohd Amin and Zarina Abu Bakar - Kadri, Mohd Halim; Mohd Amin, Juyati; Abu Bakar, Zarina (2021)
The goal of this study is to look at the value relevance of accounting policy for an investment property of Malaysian listed companies. The sample was drawn from Malaysian publicly traded companies using simple random sampling to ensure that all publicly traded companies had an equal probability of being chosen. From 2018 to 2019, a final sample of 108 firm-years from diverse sectors was chosen. Landsman (1986) equity valuation method was used to analyse the value relevance of investment property used by Malaysian listed companies. The model was used to determine whether the value of a pooled sample, a fair value sample or a cost sample was valued relevant. Regardless of whether a cost model or a fair value model is used, the results suggest that enterprises' investment properties are value relevant. According to the findings, the cost model is more useful in determining the value of an investment property. The outcome gives standard setters useful information about the impact of choosing a fair value model and a cost model on share market value.